The Femoral Tunnel Drilling Angle at 45° Coronal and 45° Sagittal Provided the Lowest Peak Stress and Strain on the Bone Tunnels and Anterior Cruciate Ligament Graft - Cheng, Rongshan; Wang, Huizhi; Jiang, Ziang; Dimitriou, Dimitris; Cheng, Cheng-Kung; Tsai, Tsung-Yuan (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: The aims of this study were to (1) investigate the effects of femoral drilling angle in coronal and sagittal planes on the stress and strain distribution around the femoral and tibial tunnel entrance and the stress distribution on the graft, following anterior cruciate ligament reconstruction (ACLR), (2) identify the optimal femoral drilling angle to reduce the risk of the tunnel enlargement and graft failure. Methods: A validated three-dimensional (3D) finite element model of a healthy right cadaveric knee was used to simulate an anatomic ACLR with the anteromedial (AM) portal technique. Combined loading of 103.0 N anterior tibial load, 7.5 Nm internal rotation moment, and 6.9 Nm valgus moment during normal human walking at joint flexion of 20° was applied to the ACLR knee models using different tunnel angles (30º/45º/60º and 45º/60º in the coronal and sagittal planes, respectively). The distribution of von Mises stress and strain around the tunnel entrances and the graft was calculated and compared among the different finite element ACLR models with varying femoral drilling angles. Results: With an increasing coronal obliquity drilling angle (30º to 60º), the peak stress and maximum strain on the femoral and tibial tunnel increased from 30º to 45º and decreased from 45º to 60º, respectively. With an increasing sagittal obliquity drilling angle (45º to 60º), the peak stress and the maximum strain on the bone tunnels increased. The lowest peak stress and maximum strain at the ACL tunnels were observed at 45° coronal/ 45° sagittal drilling angle (7.5 MPa and 7568.3 μ-strain at the femoral tunnel entrance, and 4.0 MPa and 4128.7 μ-strain at the tibial tunnel entrance). The lowest peak stress on the ACL graft occurred at 45° coronal/ 45° sagittal (27.8 MPa) drilling angle. Conclusions: The femoral tunnel drilling angle could affect both the stress and strain distribution on the femoral tunnel, tibial tunnel, and graft. A femoral tunnel drilling angle of 45° coronal/ 45° sagittal demonstrated the lowest peak stress, maximum strain on the femoral and tibial tunnel entrance, and the lowest peak stress on the ACL graft.